PREFIKS SE-BAHASA INDONESIA DAN PADANANNYA DALAM BAHASA SUWAWA - Sri Nurlaela Sabubu (TELAGA BAHASA, 2017)
This paper aimed to examine the shape and meaning of prefix se- inIndonesian and their equivalents and describe their function in Suwawalanguage. This research was descriptive based on the theory of Keraf andChaer in Affixation. The analyzed data in this research was DictionaryBahasa Indonesia - Suwawa compiled by Prof. Mansoer Pateda and YennieP. Pulubuhu. It was found that from seventh meaning/function of pfefiks se-in Bahasa Indonesia, there are four functions that have no similar meaningor function in Suwawa language, which are: ‘declare all’ or ‘entire’; toexpress the meaning of ‘resembling or ‘like’; to declare ‘amount’; andimplies ‘the most’.